Proximate sharing of geo data using the credit‐considered mobile edge computing server switching control scheme. (8th June 2020) - Huang, Chung‐Ming; Chen, Pin‐Jui
Summary: This paper proposed a mobile edge computing (MEC)‐based point of interests (POIs) downloading and proximate sharing system for a group of people, who belong to the same mobile social networks in proximity (MSN‐P) and whose handheld devices are connected in a tree‐like structure. Using the proposed system, the root handheld device plays the role of an MEC server and is charge of downloading POIs' contents from the remote cloud server using 4G/5G cellular network and then forwarding POIs' contents to other group members' handheld devices using device‐to‐device (D2D) communication. Since the number of connected handheld devices in each handheld device is limited using D2D communication, this work proposed a control scheme called k‐Connection‐Limited and n‐Hop (kCL‐nH) tree topology's construction scheme to achieve the proximate sharing of POIs' contents. Additionally, since the root handheld device consumes more battery power than others, this work proposed a control scheme that has each group member's handheld device to be the root handheld device alternatively. A credit scheme was thus proposed to denote each handheld device's contribution, which is referred for the selecting of the next root handheld device, to achieve the fairness concern. Then, the control scheme, which is executed in the corresponding MEC server, considering both remaining battery power and credit for the switching of the root handheld device was designed. The proposed method was developed using Wi‐Fi Direct over the iOS system. Experimental results have shown some interested results among power consumption, downloaded data volume and fairness among all handheld devices.